(untitled) - Paulo Ricardo Criado; Lívia Delgado; Gustavo Alonso Pereira (Sociedade Brasileira de Dermatologia, 2013)
Dermoscopy has being used over the past twenty years as a noninvasive aid in the diagnosis of innumerable skin conditions, including infectious diseases and infestations (Entodermoscopy).Tinea nigra is a superficial phaeohyfomycosis that affects mainly the glabrous skin of palms and soles. We describe a 14 year-old girl with a three-month history of an enlarging brown patch of her hand diagnosed as Tinea Nigra following clinical and dermoscopy examination.These images emphasize the importance of dermoscopy as a diagnostic tool in the daily routine of dermatologists. Nos últimos anos, a dermatoscopia tem sido utilizada como importante ferramenta auxiliar no diagnóstico de inúmeras dermatoses, incluindo infecções e infestações (Entodermatoscopia). A Tinea nigra é uma feoifomicose rara, que afeta principalmente a pele glabra das palmas e plantas. Descrevemos o caso de doente de 14 anos, com mácula pigmentada de crescimento progressivo na mão esquerda, diagnosticada como Tinea nigra após o exame clínico e dermatoscópico. Estas imagens enfatizam a importância da dermatoscopia na prática dermatológica diária.